The Utilization of Lapindo Mud Waste for Aluminium Sulfate Production - Lucky Indrati Utami; Tahan Simamora Rizaldi; Kindriari Nurma Wahyusi; Reva Edra Nugraha (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2021)
The Lapindo mudflow disaster in East Java Province, or also known as LUSI (LUmpur “mud”-SIdoarjo) has become spectacular longest ongoing disaster in recent memory since 2006. The utilization of volcanic Lapindo mud could be the promising solution to prevent further environmental damage. The chemical composition of Lapindo mud contained of 44.1% SiO2, 23.7% Fe2O3, 13% Al2O3, 7.02% CaO, 5.35% MoO3, 2.53% K2O, 1.84% TiO2 and 0.7% Na2O. Aluminium sulfate (Al2(SO4)3) or “alum” have been widely used as coagulation compound in water treatment, paper and textiles industry. Aluminium sulfate can be synthesized from aluminium oxide (Al2O3) from Lapindo mud with acidic solutions (H2SO4). The aim of this work was to synthesize aluminum sulfate from Lapindo mud by using extraction process. The impact of H2SO4 concentration and heating time to the production of aluminium sulfate have been investigated. The results showed that the aluminium sulfate can be synthesized from Lapindo mud by using H2SO4. Based on XRF analysis, the variation of heating time and H2SO4 concentration affect the aluminium sulfate conversion. The increasing of heating time and H2SO4 concentration directly enhance the conversion until reach the optimum condition. The optimum condition for aluminium sulfate synthesis from Lapindo mud (75.78% conversion) was found to be 90 min for heating time with H2SO4 concentration of 80%.